The Law Applicable to Arbitration Agreements in Light of the Decision of the German Federal Court Dated 9 March 2023 on the Refusal to Enforce A Foreign Arbitral Award Against Third Parties and Recent Developments - Banu Şit Köşgeroğlu (Public and Private International Law Bulletin)
This study covers the implied choice of law and the role of the law applicable to the main contract in determining the law to be applied to the arbitration agreement. Recently, high courts in various legal systems have shown different tendencies regarding this issue. A decision made by the German Federal Court on March 9, 2023 is remarkable in this sense. In the decision, it was accepted that the law applicable to the arbitration agreement was implicitly chosen, and the English Supreme Court previously gave similar decisions. In some other legal systems, it is observed that the law applicable to the arbitration agreement is determined by making implied choice of law and/or the most closely connected law evaluations. The fact that the English Law Commission has recently proposed a law change that eliminates the implied choice of law reveals that legal certainty should be emphasized in this regard.